INDUSTRIAL NOISE POLLUTION AND ITS EFFECTS ON HUMAN HEALTH (PANGEEA, 2025)
The development of industrial activities has led to a diversification of noise sources and to higher sound pressure levels. Although it is considered as being a pollutant, noise is the only pollutant that does not leave residual traces in the environment. Miscellaneous research papers conducted in the last years have shown that noise exposure triggers different kind of health problems, some of them being not extensively studied yet. Also, it was found that people react differently to noise exposure and so far there were not identified accurate correlations between different levels of exposure and the occurrence of certain health problems. This study aims to identify the main industrial noise sources, the impact of noise on human health, the noise measurement methods, the maximum admitted values for noise in Romania and also few methods that can be used to decrease the noise level.
Keywords: noise pollution; industrial noise